PENGARUH PEMBELAJARAN OUTDOOR STUDY TERHADAP SIKAP KEPEDULIAN LINGKUNGAN BAGI MAHASISWA S1 PENDIDIKAN GEOGRAFI STKIP AHLUSSUNAH BUKITTINGGI - Andini, Nisye Frisca (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2018)
This study aims to determine the effect of outdoor learning on the attitude of environmental care for students of Geography Education in STKIP Ahlussunah Bukittinggi. This research is an experiment to assess the effect of the educational approach on student’s attitudes and behavior before and after the treatment being given. Referred to the homogeneity test on students' cognitive ability result, it can be concluded that the characters of the subject research were homogeneous. The determination of the experimental and the control class could be done by using a random method. The result of the study shows that the implementation of the outdoor learning can improve student’s awareness toward the environment. It is detected by the significant difference of the tests results between the control class and the experimental class. The using of outdoor class approach is proven to enhance the quality of students’ attitudes in environmental learning material, because it motivates students during the learning process